Traditional Agroforestry Models Based on Local Knowledge in the Mount Mutis-Timau Highlands,Timor Island, Indonesia - Dako, Fransiskus Xaverius; Ora, Yudhistira A.N.R.; Ranta, Fabianus; Benu, Yakub; Paga, Blasius; Aramak, Fredik S.; Pujiono, Eko (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
The adoption of local knowledge in land management is a fundamental aspect that determines the success of managing agroforestry systems to support food security and improve community welfare. This study aims to examine the application of local community knowledge in managing owned land using an agroforestry model. Data were collected through a series of systematic stages, including indepth interviews with respondents who were heads of households and community leaders, direct observation of the land, and literature studies related to agroforestry patterns. A descriptive analysis using a qualitative approach was conducted to obtain important information regarding the actual conditions observed. The results show that the construction of local knowledge is determined using space by intervening with various plants on a plot of land. The crop planting intervention consisted of three models: intercropping, annual/plantation plants as a fence dividing the land, and forestry plants separated from agricultural/plantation plants. Farmers in Ajaobaki and Fatumnasi Villages choose seasonal crops (corn and beans) to meet food needs, plantation crops (Aleurites moluccana (L.) Willd, Citrus reticulata, Persea americana, Artocarpus heterophyllus, and Mangifera indica) to increase income and ecological functions, and forestry crops (Casuarina junghuhniana,Eucalyptus urophylla, Tectona grandis L.f, and Gmelina arborea), which provide both economic and ecological benefits. Planting a combination of plant types on land can indirectly anticipate climate change and, on the other hand, can improve community welfare and protect the environment in the area.